Evidence of Disseminated Intravascular Coagulation in a Porcine Model Following Radiation Exposure - Krigsfeld, G.S. (2014)
Recent evidence has suggested that disseminated intravascular coagulation (DIC) plays an integral role in death at the LD(50) dose of either gamma or solar particle event (SPE)-like proton radiation in ferrets. In these studies, Yucatan minipigs were evaluated to determine whether they were susceptible to the development of radiation induced DIC. Yucatan minipigs were exposed to a dose of 2.5 Gray (Gy) with x-rays and monitored over the course of 30 days. Evidence of DIC was evaluated by way of thromboelastometry parameters, platelet counts, fibrinogen concentration, and the d-dimer assay. Pigs exposed to x-rays developed signs of DIC within 2 days post-irradiation. The development of DIC was exacerbated over the course of the studies, and one of the pigs died at day 14 and another had to be euthanized on day 16 post-irradiation. For both of these pigs, DIC was evident at the time of death. The following observations were indicated or were suggestive of DIC: whole blood clotting was impaired (as evidenced by thromboelastometry alterations), there were decreased platelet counts, elevated d-dimer concentrations in the blood, and/or hemorrhaging and the presence of fibrin in tissues observed during post-mortem examination. The extrapolation of data from these studies, in combination with other published data, have led to the hypothesis that there could be a correlation between the propensity to develop DIC, as indicated by hemorrhaging at death at relatively low doses of radiation, and the LD(50) for a particular species. Our data suggest that the development of DIC may contribute to death at the LD(50) dose in large mammals.